Articular cartilage repair with recombinant human type II collagen/polylactide scaffold in a preliminary porcine study. Issue 5 (26th November 2015) - Muhonen, Virpi; Salonius, Eve; Haaparanta, Anne‐Marie; Järvinen, Elina; Paatela, Teemu; Meller, Anna; Hannula, Markus; Björkman, Mimmi; Pyhältö, Tuomo; Ellä, Ville; Vasara, Anna; Töyräs, Juha; et al.
ABSTRACT: The purpose of this study was to investigate the potential of a novel recombinant human type II collagen/polylactide scaffold (rhCo‐PLA) in the repair of full‐thickness cartilage lesions with autologous chondrocyte implantation technique (ACI). The forming repair tissue was compared to spontaneous healing (spontaneous) and repair with a commercial porcine type I/III collagen membrane (pCo). Domestic pigs (4‐month‐old, n  = 20) were randomized into three study groups and a circular full‐thickness chondral lesion with a diameter of 8 mm was created in the right medial femoral condyle. After 3 weeks, the chondral lesions were repaired with either rhCo‐PLA or pCo together with autologous chondrocytes, or the lesion was only debrided and left untreated for spontaneous repair. The repair tissue was evaluated 4 months after the second operation. Hyaline cartilage formed most frequently in the rhCo‐PLA treatment group. Biomechanically, there was a trend that both treatment groups resulted in better repair tissue than spontaneous healing. Adverse subchondral bone reactions developed less frequently in the spontaneous group (40%) and the rhCo‐PLA treated group (50%) than in the pCo control group (100%). However, no statistically significant differences were found between the groups. The novel rhCo‐PLA biomaterial showed promising results in this proof‐of‐concept study, but further studies will be needed in order to determine its effectiveness in articular cartilage repair. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:745–753, 2016.